Case Report: Altered NK Cell Compartment and Reduced CXCR4 Chemotactic Response of B Lymphocytes in an Immunodeficient Patient With HPV-Related Disease - Doria, Margherita; Moscato, Giusella M. F.; Di Cesare, Silvia; Di Matteo, Gigliola; Sgrulletti, Mayla; Bachelerie, Françoise; Marin-Esteban, Viviana; Moschese, Viviana (Frontiers in Immunology, 2022)
The study of inborn errors of immunity (IEI) provides unique opportunities to elucidate the microbiome and pathogenic mechanisms related to severe viral infection. Several immunological and genetic anomalies may contribute to the susceptibility to develop Human Papillomavirus (HPV) pathogenesis. They include different acquired immunodeficiencies, EVER1-2 or CIB1 mutations underlying epidermodysplasia verruciformis (EV) syndrome and multiple IEI. Whereas EV syndrome patients are specifically unable to control infections with beta HPV, individuals with IEI show broader infectious and immune phenotypes. The WHIM (warts, hypogammaglobulinemia, infection, and myelokathexis) syndrome caused by gain-of-CXCR4-function mutation manifests by HPV-induced extensive cutaneous warts but also anogenital lesions that eventually progress to dysplasia. Here we report alterations of B and NK cells in a female patient suffering from cutaneous and mucosal HPV-induced lesions due to an as-yet unidentified genetic defect. Despite no detected mutations in CXCR4, B but not NK cells displayed a defective CXCR4-dependent chemotactic response toward CXCL12. In addition, NK cells showed an abnormal distribution with an expanded CD56bright cell subset and defective cytotoxicity of CD56dim cells. Our observations extend the clinical and immunological spectrum of IEI associated with selective susceptibility toward HPV pathogenesis, thus providing new insight on the immune control of HPV infection and potential host susceptibility factors.